The Ethical Values in Islamic Tradition Reinterpreting Morals in the Context of Global Moral Crisis - Elystia Febriyanti; Nur Kholid; Muh. Dzihab Aminudin S; Rudi Hartono (CV. Creative Tugu Pena, 2025)
This article explores the ethical values within the Islamic tradition as a meaningful response to the contemporary global moral crisis, which permeates various dimensions of modern human life. Employing a qualitative-critical approach through library research, this study delves into classical and contemporary Islamic ethical texts, particularly the works of seminal thinkers such as Al-Ghazali, Ibn Miskawayh, and Al-Raghib Al-Isfahani. The findings reveal that Islamic ethics are not solely anchored in the normative framework of Shari'a, but also encompass profound spiritual dimensions and universal moral consciousness. Core values such as honesty (ṣidq), justice (ʿadl), trustworthiness, and compassion (raḥmah) are demonstrated to retain enduring relevance across diverse contemporary global contextsranging from politics and economics to intercultural relations. The article advocates for a dynamic reinterpretation of these transhistorical ethical principles to address pressing modern issues such as rampant individualism, systemic corruption, and the erosion of empathy. The study's implications extend beyond the field of Islamic studies, contributing to a broader, inclusive global ethical discourse grounded in religious moral traditions. Ultimately, the article calls for a revitalization of Islamic ethical values in education, public policy, and societal life to help shape a more just, compassionate, and spiritually enriched world.